Quaternary phosphorus salt ionic liquid loaded polyurethane-based catalyst and preparation method thereof
By constructing a catalyst for active metal single atoms and quaternary phosphorus salt ionic liquid on a polyurethane support, the inefficiency problem of cycloaddition reaction between CO2 and epoxide in the prior art is solved, and efficient and low-cost cyclic carbonate synthesis is achieved.
Patent Information
- Application Number
- CN202411750604.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to efficiently catalyze the cycloaddition reaction between CO2 and epoxide under low temperature and normal pressure, solvent-free and promoter-free conditions, and the separation of catalysts and product purification are complex.
Through radical polymerization and ionization treatment, a polyurethane-based catalyst supported by quaternary phosphorus salt ionic liquid is prepared. The catalyst contains active metal single atoms and quaternary phosphorus salt ionic liquids, which can achieve flexible construction of metal single atom sites and grafting of quaternary phosphorus salt ions on the polyurethane support.
The synthesis of cyclic carbonate of CO2 and epoxides with high activity, high selectivity and high stability under low temperature and normal pressure, solvent-free and no promoter conditions is achieved, thereby reducing production input and product separation and purification costs.
Smart Images

Figure CN119569982A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis, and particularly relates to a quaternary phosphonium salt ionic liquid-loaded polyurethane-based catalyst and a preparation method thereof. Background Art
[0002] As a cheap, readily available, non-toxic and renewable C1 resource, the study of the catalytic conversion of CO2 can not only reduce CO2 emissions, but also convert it into high-value-added chemical and energy products, achieving the goal of turning waste into treasure and resource utilization. In the study of CO2 conversion, the synthesis of cyclic carbonates using cheap epoxides and CO2 as raw materials is an important way to achieve efficient resource utilization of CO2. The reaction achieves 100% atomic utilization, and its product cyclic carbonates are widely used as important chemical products in high-boiling polar solvents, lithium-ion battery electrolytes, polymer materials, etc.
[0003] At present, CO2 cycloaddition heterogeneous catalysts have received extensive attention and research, among which atomically dispersed high-density metal single atom sites on porous supports can efficiently catalyze CO2 cycloaddition reactions. However, since CO2 cycloaddition reactions involve acid-base synergistic catalytic mechanisms, organic nucleophilic homogeneous co-catalysts (such as tetrabutylammonium halide TBAX, X = Br, Cl, I) are usually required during the reaction, making the separation of catalysts and product purification complicated. Therefore, how to construct multifunctional catalysts through precise structural design to achieve efficient CO2 cycloaddition reactions and simple product separation under low temperature and normal pressure, solvent-free, and co-catalyst-free conditions is an important direction worthy of research in this field. Summary of the invention
[0004] The key technical problem to be solved by the present invention is to provide an efficient CO2 cycloaddition catalyst with simple preparation process, low production cost and easy recycling. Furthermore, the catalyst can catalyze CO2 and epoxide to synthesize cyclic carbonate with high activity, high selectivity and high stability under low temperature and normal pressure, solvent-free and catalyst-free conditions.
[0005] The present invention provides a method for preparing a polyurethane-based catalyst supported by a quaternary phosphonium salt ionic liquid. The polyurethane-based catalyst composited with an active metal single atom and a quaternary phosphonium salt ionic liquid can be obtained by simple free radical polymerization and ionization treatment. The method comprises the following steps:
[0006] (1) dissolving appropriate amounts of metal precursor, triethanolamine, hydroxyethyl methacrylate and p-chloromethylstyrene in an organic reagent to obtain a solution A;
[0007] (2) dissolving an appropriate amount of p-phenylene diisocyanate in an organic reagent to obtain a solution B;
[0008] (3) Under the protection of inert gas, solution A and solution B are fully mixed and stirred at a constant temperature until gelation occurs. Stirring is stopped and the mixture is quickly transferred to a transparent mold for shaping. Subsequently, the gel is evenly exposed to strong light for photosensitive activation treatment;
[0009] (4) Further, the gel is subjected to constant temperature aging treatment to improve its mechanical strength; after the aging is completed, the excess organic reagent on the catalyst surface is removed to obtain polyurethane precursors of various shapes;
[0010] (5) dispersing the above polyurethane precursor and an appropriate amount of phosphorus-containing ionic liquid monomer in an appropriate amount of organic solvent, and refluxing at a constant temperature under the protection of an inert gas to graft the quaternary phosphonium salt ionic liquid; finally, removing the organic reagent on the surface of the sample, washing it alternately with deionized water and anhydrous ethanol, and drying it to obtain the quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst M-IL-PU;
[0011] (6) M-IL-PU and an appropriate amount of epoxide are placed in a reactor, CO2 is continuously introduced to replace the air in the reaction system, and then CO2 and epoxide are subjected to cycloaddition reaction at low temperature and normal pressure to prepare cyclic carbonate; after the reaction is completed, the reaction system is cooled to room temperature, M-IL-PU is directly taken out, and it is washed three times with deionized water and anhydrous ethanol before recycling; the liquid product is qualitatively and quantitatively analyzed by gas chromatography and nuclear magnetic resonance, and the substrate conversion rate and the selectivity of the target product cyclic carbonate are calculated.
[0012] Among them, the reaction equation for preparing cyclic carbonate by cycloaddition of CO2 and epoxide under normal pressure is as follows:
[0013]
[0014] The schematic diagram of the structure of the polyurethane-based catalyst supported by the quaternary phosphonium salt ionic liquid is as follows:
[0015]
[0016] Preferably, in step (1), the types of metal precursors include but are not limited to metal oxides, metal chlorides, carbonates, sulfates, acetates; the types of metals include but are not limited to Co, Zn, Ti, Al, Mg; the concentration of the metal precursor is 0.001 to 1 mol / L; the concentration of triethanolamine is 0.01 to 10 mol / L; the concentration of hydroxyethyl methacrylate is 0.01 to 10 mol / L; the concentration of p-chloromethylstyrene is 0.01 to 10 mol / L.
[0017] Preferably, in step (2), the concentration of p-phenylene diisocyanate is 0.01 to 10 mol / L.
[0018] Preferably, in steps (1), (2) and (5), the organic reagent includes but is not limited to a mixture of one or more organic reagents, and the types of organic reagents include but are not limited to acetonitrile, tetrahydrofuran, 1,4-dioxane, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, methanol, and ethanol.
[0019] Preferably, in steps (3) and (5), the inert gas includes but is not limited to argon, nitrogen, and helium; the temperature of the constant temperature stirring in step (3) is 10 to 90° C., the stirring rate is 50 to 1000 rpm, and the stirring time is 10 to 1000 s; the light source for the photosensitization treatment includes but is not limited to mercury lamp, xenon lamp, LED lamp, laser, and the illumination time is 5 to 300 min.
[0020] Preferably, in step (4), the constant temperature aging temperature is 10-120°C, and the aging time is 1-168h; the shape of the catalyst includes but is not limited to block, sheet, strip, and film; the volume of the catalyst is 1-100000cm 2 .
[0021] Preferably, in step (5), the types of the phosphorus-containing ionic liquid monomers include but are not limited to triphenylphosphine, tri(o-tolyl)phosphine, tri-p-tolylphosphine, and tributylphosphine, and the concentration is 0.01 to 10 mol / L; the temperature of the reflux treatment is 20 to 120° C., and the reflux time is 4 to 48 h.
[0022] Preferably, in steps (4) and (5), the method for removing the organic solvent on the catalyst surface includes but is not limited to volatilization at room temperature and normal pressure, vacuum drying, forced air drying, and freeze drying.
[0023] Preferably, in step (6), the types of epoxides include but are not limited to ethylene oxide, propylene oxide, epichlorohydrin, epibromohydrin, styrene oxide, and 1,2-butylene oxide; the reaction temperature is 20 to 120° C., and the reaction time is 2 to 40 hours.
[0024] The present invention also provides a polyurethane-based catalyst loaded with a quaternary phosphonium salt ionic liquid prepared by the above preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst provided by the present invention has the advantages of simple synthesis operation, low preparation cost, and easy recycling compared with powder-type catalysts.
[0027] (2) The polyurethane-based catalyst supported by quaternary phosphonium salt ionic liquid provided by the present invention successfully realizes the flexible construction of atomically dispersed metal single atom sites on the polyurethane carrier and the grafting of quaternary phosphonium salt ionic liquid, which is beneficial to the rapid adsorption of epoxide on the catalyst surface and promotes the ring-opening process, avoids the use of homogeneous co-catalyst (tetrabutylammonium halide), greatly reduces the production input and product separation and purification costs, and is more suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The polyurethane catalyst supported by the quaternary phosphonium salt ionic liquid synthesized in Examples 1-3.
[0029] Figure 2 The stability test results of Zn-IL-PU-1 in Example 1. DETAILED DESCRIPTION
[0030] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] (1) 0.1 mmol zinc acetate, 3.3 mmol triethanolamine, 1.3 mmol hydroxyethyl methacrylate and 1.3 mmol p-chloromethylstyrene were ultrasonically dispersed in 4 mL DMF to obtain solution A.
[0033] (2) 6 mmol of p-phenylene diisocyanate was ultrasonically dispersed in 16 mL of DMF to obtain solution B.
[0034] (3) Solution A and Solution B were fully mixed under an Ar atmosphere and stirred at a constant temperature of 30°C until gelation occurred. Stirring was stopped and the gel was quickly transferred to a centrifuge tube for shaping. Subsequently, the gel was uniformly exposed to a xenon lamp, and after being treated with light for 2 hours, it was placed in a 60°C oven for constant temperature aging for 24 hours. Furthermore, the aged gel was placed in a 60°C vacuum oven to remove excess organic reagents to obtain a block-shaped polyurethane precursor.
[0035] (4) The precursor and 1.3 mmol of triphenylphosphine were dispersed in 30 mL of methanol and refluxed at 60 °C for 12 h under Ar protection to graft the quaternary phosphonium salt ionic liquid. Finally, the sample was placed in a vacuum oven at 60 °C to remove excess organic reagents, and the Zn-IL-PU-1 catalyst was obtained after alternately washing with deionized water and anhydrous ethanol and drying.
[0036] (5) Place Zn-IL-PU-1 in a reactor, add 5 mL of epichlorohydrin, and continuously introduce 100% pure CO2 gas to replace the air in the system, maintaining the pressure in the reactor at 1 bar. After sealing the reactor, raise the temperature to 50°C, start the reaction, and react for 6 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, take out Zn-IL-PU-1 directly, wash it three times with deionized water and anhydrous ethanol, and dry it for 3 hours before performing a cycle test. The liquid product was qualitatively and quantitatively analyzed by gas chromatography. The results showed that the conversion rate of epichlorohydrin was 97.6% and the product selectivity was as high as 99.2%. After 5 cycle tests, Zn-IL-PU-1 still showed a substrate conversion rate of 93.3% and a product selectivity of 98.7%.
[0037] Embodiment 2:
[0038] (1) 0.1 mmol zinc acetate, 2.6 mmol triethanolamine, 2.6 mmol hydroxyethyl methacrylate and 2.6 mmol p-chloromethylstyrene were ultrasonically dispersed in 4 mL DMF to obtain solution A.
[0039] (2) 6 mmol of p-phenylene diisocyanate was ultrasonically dispersed in 16 mL of DMF to obtain solution B.
[0040] (3) Solution A and Solution B were fully mixed under an Ar atmosphere and stirred at a constant temperature of 30°C until gelation occurred. Stirring was stopped and the gel was quickly transferred to a centrifuge tube for shaping. Subsequently, the gel was uniformly exposed to a xenon lamp, and after being treated with light for 2 hours, it was placed in a 60°C oven for constant temperature aging for 24 hours. Furthermore, the aged gel was placed in a 60°C vacuum oven to remove excess organic reagents to obtain a block-shaped polyurethane precursor.
[0041] (4) The precursor and 2.6 mmol of triphenylphosphine were dispersed in 30 mL of methanol and refluxed at 60 °C for 12 h under Ar protection to graft the quaternary phosphonium salt ionic liquid. Finally, the sample was placed in a vacuum oven at 60 °C to remove excess organic reagents, and the Zn-IL-PU-2 catalyst was obtained after alternately washing with deionized water and anhydrous ethanol and drying.
[0042] (5) Place Zn-IL-PU-2 in a reactor, add 5 mL of epichlorohydrin, and continuously introduce 100% pure CO2 gas to replace the air in the system, maintaining the pressure in the reactor at 1 bar. After sealing the reactor, raise the temperature to 50°C, start the reaction, and react for 6 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, directly take out Zn-IL-PU-2, wash it three times with deionized water and anhydrous ethanol, and then dry it for 3 hours before recycling. The liquid product was qualitatively and quantitatively analyzed by gas chromatography. The results showed that the conversion rate of epichlorohydrin was 99.6%, and the product selectivity was as high as 99.6%.
[0043] Embodiment 3:
[0044] (1) 0.1 mmol of aluminum chloride, 2.6 mmol of triethanolamine, 2.6 mmol of hydroxyethyl methacrylate and 2.6 mmol of p-chloromethylstyrene were ultrasonically dispersed in 4 mL of DMF to obtain solution A.
[0045] (2) 6 mmol of p-phenylene diisocyanate was ultrasonically dispersed in 16 mL of DMF to obtain solution B.
[0046] (3) Solution A and Solution B were fully mixed under an Ar atmosphere and stirred at a constant temperature of 30°C until gelation occurred. Stirring was stopped and the gel was quickly transferred to a centrifuge tube for shaping. Subsequently, the gel was uniformly exposed to a xenon lamp, and after light treatment for 3 hours, it was placed in a 60°C oven for constant temperature aging for 24 hours. Furthermore, the aged gel was placed in a 60°C vacuum oven to remove excess organic reagents to obtain a block-shaped polyurethane precursor.
[0047] (4) The precursor and 2.6 mmol of triphenylphosphine were dispersed in 30 mL of methanol and refluxed at 50 °C for 6 h under Ar protection to graft the quaternary phosphonium salt ionic liquid. Finally, the sample was placed in a vacuum oven at 60 °C to remove excess organic reagents, and the Al-IL-PU catalyst was obtained after alternately washing with deionized water and anhydrous ethanol and drying.
[0048] (5) Place Al-IL-PU in a reactor, add 5 mL of epichlorohydrin, and continuously introduce 100% pure CO2 gas to replace the air in the system, maintaining the pressure in the reactor at 1 bar. After sealing the reactor, raise the temperature to 50°C, start the reaction, and react for 6 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, take out Al-IL-PU directly, wash it three times with deionized water and anhydrous ethanol, and then dry it for 3 hours before recycling. The liquid product was qualitatively and quantitatively analyzed by gas chromatography. The results showed that the conversion rate of epichlorohydrin was 94.6%, and the product selectivity was as high as 98.6%.
[0049] Embodiment 4:
[0050] (1) 0.1 mmol of titanium tetrachloride, 3.3 mmol of triethanolamine, 1.3 mmol of hydroxyethyl methacrylate and 1.3 mmol of p-chloromethylstyrene were ultrasonically dispersed in 4 mL of DMF to obtain solution A.
[0051] (2) 6 mmol of p-phenylene diisocyanate was ultrasonically dispersed in 16 mL of DMF to obtain solution B.
[0052] (3) Solution A and Solution B were fully mixed under an Ar atmosphere and stirred at a constant temperature of 30°C until gelation occurred. Stirring was stopped and the gel was quickly transferred to a centrifuge tube for shaping. Subsequently, the gel was uniformly exposed to a xenon lamp, and after being treated with light for 2 hours, it was placed in a 60°C oven for constant temperature aging for 24 hours. Furthermore, the aged gel was placed in a 60°C vacuum oven to remove excess organic reagents to obtain a block-shaped polyurethane precursor.
[0053] (4) The precursor and 1.3 mmol of triphenylphosphine were dispersed in 30 mL of methanol and refluxed at 60 °C for 10 h under Ar protection to graft the quaternary phosphonium salt ionic liquid. Finally, the sample was placed in a vacuum oven at 60 °C to remove excess organic reagents, and the Ti-IL-PU catalyst was obtained after alternately washing with deionized water and anhydrous ethanol and drying.
[0054] (5) Place Ti-IL-PU in a reactor, add 5 mL of epichlorohydrin, and continuously introduce 100% pure CO2 gas to replace the air in the system, maintaining the pressure in the reactor at 1 bar. After sealing the reactor, raise the temperature to 50°C, start the reaction, and react for 8 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, take out Ti-IL-PU directly, wash it three times with deionized water and anhydrous ethanol, and then recycle it after drying for 3 hours. The liquid product was qualitatively and quantitatively analyzed by gas chromatography. The results showed that the conversion rate of epichlorohydrin was 96.1% and the product selectivity was as high as 98.9%.
[0055] Embodiment 5:
[0056] The catalyst preparation process and experimental operation steps of Example 5 are the same as those of Example 2, except that the high-purity CO2 (100%) is replaced by industrial simulated flue gas (15% CO2 + 85% N2), and the reaction time is extended to 24 hours. The results show that the conversion rate of epichlorohydrin is 90.4%, and the product selectivity reaches 99.5%.
[0057] Embodiment 6:
[0058] The catalyst preparation process and experimental operation steps of Example 6 are the same as those of Example 2, except that triphenylphosphine is replaced by an equal amount of tri(o-tolyl)phosphine to prepare Zn-IL-PU-3, and the reaction time is extended to 8 hours. The results show that the conversion rate of epichlorohydrin is 94.8%, and the product selectivity reaches 99.7%.
[0059] Embodiment 7:
[0060] The catalyst preparation process and experimental operation steps of Example 7 are the same as those of Example 2, except that high-purity CO2 (100%) is replaced by air, and air is continuously introduced during the reaction at a flow rate of 10 mL / min, and the reaction time is extended to 40 h. The results show that the conversion rate of epichlorohydrin is 59.6%, and the product selectivity reaches 98.9%.
[0061] Embodiment 8:
[0062] The preparation process and experimental operation steps of Zn-IL-PU-2 were the same as those in Example 2, except that epichlorohydrin was replaced by cyclopentene oxide, and the reaction time was extended to 9 hours. The results showed that the conversion rate of cyclopentene oxide was 91.4%, and the product selectivity was 98.8%.
[0063] Embodiment 9:
[0064] The preparation process and experimental operation steps of Zn-IL-PU-2 were the same as those in Example 2, except that epichlorohydrin was replaced by epibromohydrin, and the reaction time was extended to 10 h. The results showed that the conversion rate of epibromohydrin was 93.3% and the product selectivity was 99.0%.
[0065] Embodiment 10:
[0066] The preparation process and experimental operation steps of Zn-IL-PU-2 were the same as those in Example 2, except that epichlorohydrin was replaced by phenyl glycidyl ether, and the reaction time was extended to 12 h. The results showed that the conversion rate of phenyl glycidyl ether was 90.8%, and the product selectivity was 98.8%.
[0067] The specific evaluation results of the catalysts of Examples 1-10 are shown in Table 1 below.
[0068] Table 1 Specific evaluation results of catalysts of Examples 1-10
[0069]
[0070] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyurethane-based catalyst supported by a quaternary phosphonium salt ionic liquid, characterized in that: A polyurethane-based catalyst composited with active metal single atoms and quaternary phosphonium salt ionic liquid can be obtained by simple free radical polymerization and ionization treatment. The method comprises the following steps: (1) dissolving appropriate amounts of metal precursor, triethanolamine, hydroxyethyl methacrylate and p-chloromethylstyrene in an organic reagent to obtain a solution A; (2) dissolving an appropriate amount of p-phenylene diisocyanate in an organic reagent to obtain a solution B; (3) Under the protection of inert gas, solution A and solution B are fully mixed and stirred at a constant temperature until gelation occurs. Stirring is stopped and the mixture is quickly transferred to a transparent mold for shaping. Subsequently, the gel is evenly exposed to strong light for photosensitive activation treatment; (4) Further, the gel is subjected to constant temperature aging treatment to improve its mechanical strength; after the aging is completed, the excess organic reagent on the catalyst surface is removed to obtain polyurethane precursors of various shapes; (5) dispersing the above polyurethane precursor and an appropriate amount of phosphorus-containing ionic liquid monomer in an appropriate amount of organic solvent, and refluxing at a constant temperature under the protection of an inert gas to graft the quaternary phosphonium salt ionic liquid; finally, removing the organic reagent on the surface of the sample, washing it alternately with deionized water and anhydrous ethanol, and drying it to obtain the quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst M-IL-PU; (6) M-IL-PU and an appropriate amount of epoxide are placed in a reactor, CO2 is continuously introduced to replace the air in the reaction system, and then CO2 and epoxide are subjected to cycloaddition reaction at low temperature and normal pressure to prepare cyclic carbonate; after the reaction is completed, the reaction system is cooled to room temperature, M-IL-PU is directly taken out, and it is washed three times with deionized water and anhydrous ethanol before recycling; the liquid product is qualitatively and quantitatively analyzed by gas chromatography and nuclear magnetic resonance, and the substrate conversion rate and the selectivity of the target product cyclic carbonate are calculated.
2. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In step (1), the types of metal precursors include but are not limited to metal oxides, metal chlorides, carbonates, sulfates, and acetates; the types of metals include but are not limited to Co, Zn, Ti, Al, and Mg; the concentration of the metal precursor is 0.001 to 1 mol / L; the concentration of triethanolamine is 0.01 to 10 mol / L; the concentration of hydroxyethyl methacrylate is 0.01 to 10 mol / L; and the concentration of p-chloromethylstyrene is 0.01 to 10 mol / L.
3. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In step (2), the concentration of p-phenylene diisocyanate is 0.01 to 10 mol / L.
4. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In steps (1), (2) and (5), the organic reagent includes but is not limited to a mixture of one or more organic reagents, and the types of organic reagents include but are not limited to acetonitrile, tetrahydrofuran, 1,4-dioxane, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, methanol, and ethanol.
5. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In steps (3) and (5), the inert gas includes but is not limited to argon, nitrogen, and helium; the temperature of the constant temperature stirring in step (3) is 10 to 90°C, the stirring rate is 50 to 1000 rpm, and the stirring time is 10 to 1000 s; the light source for the photosensitization treatment includes but is not limited to mercury lamp, xenon lamp, LED lamp, laser, and the illumination time is 5 to 300 min.
6. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In step (4), the constant temperature aging temperature is 10-120°C, and the aging time is 1-168h; the shape of the catalyst includes but is not limited to block, sheet, strip, and film; the volume of the catalyst is 1-100000cm 2 .
7. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In step (5), the types of the phosphorus-containing ionic liquid monomers include but are not limited to triphenylphosphine, tri(o-tolyl)phosphine, tri-p-tolylphosphine, and tributylphosphine, and the concentration is 0.01 to 10 mol / L; the reflux treatment temperature is 20 to 120° C., and the reflux time is 4 to 48 h.
8. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In steps (4) and (5), the method for removing the organic solvent on the catalyst surface includes but is not limited to volatilization at room temperature and normal pressure, vacuum drying, forced air drying, and freeze drying.
9. The method for preparing a quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst according to claim 1, characterized in that: In step (6), the types of epoxides include but are not limited to ethylene oxide, propylene oxide, epichlorohydrin, epibromohydrin, styrene oxide, and 1,2-butylene oxide; the reaction temperature is 20 to 120° C., and the reaction time is 2 to 40 hours.
10. A quaternary phosphonium salt ionic liquid-supported polyurethane-based catalyst, characterized in that: The catalyst is prepared by the preparation method according to any one of claims 1 to 9.